Acquisition of private ownership over land plots in Russia by virtue of acquisitive prescription: Issues and prospects. Issue 1 (31st January 2020) - Anisimov, Aleksey; Ryzhenkov, Anatoliy; Menis, Elena
Abstract : Purpose: This study aims to clarify the scope of the legal procedure of the acquisitive prescription in Russia. Design/methodology/approach: Dialectical method, historical method and system analysis method have been used. Findings: The authors consistently prove the inadmissibility of applying acquisitive prescription to land plots in private, state or municipal ownership. One of the features of Russia as an emerging market economy is that, the major part of state lands is in so-called "non-delineated state ownership." Plots included in such lands are not registered in the cadaster or transferred to particular public owners. That is why, the authors prove that the procedure of acquisitive prescription must be applied only in relation to land plots that are in non-delineated state ownership and have been occupied by citizens and legal entities for 15 years. Originality/value: The authors propose new guarantees of the rights of private and public land owners. Clarification of the scope of the acquisitive prescription procedure will streamline the turnover of real estate in Russia.